Valencia School of Sciences - Madrazo, Natividad Dulce D.; Digal, Larry N.; Concepcion, Sylvia B. (Davao City School of Management, University of the Philippines Mindanao, 2011)
Valencia School of Sciences is in its 36th year of operations and in 2010, it experienced its first net loss. The school's main course program, that is, nursing has had declining student population for the past years. Other courses like radiologic technology and physical therapy have increases in enrollment however these are not sufficient to fill in the vacuum caused by nursing. This paper uses the framework of analysis from the Strategic Planning Model suggested by Professor Miguel D. Soledad in his lecture in the Fundamentals of Strategic Management. It is a challenge to raise the enrollment of existing course programs since the latter are likewise offered in other schools in Davao City. VSS has several areas to improve on like the level of skills of the present teachers, the school?s image among students and parents, the marketing strategies being employed to attract high school graduating students, others. The External Factor Evaluation (EFE) Matrix indicates the school's inability to respond to the opportunities and threats posted by the external environment. The Internal Factor Evaluation (IFE) Matrix likewise reveals an internally weak organization. The SWOT Matrix and Quantitative Strategic Planning Matrix (QSPM) show that strategic on an intensive marketing campaign will generate the increase in student population. However these marketing efforts will be effective only when it has the support of the other functional areas.
Thesis (Master in Management)--University of the Philippines Mindanao, December 2011.